Use of Spinal Anaesthesia with Anaesthetic Block of Intercostal Nerves Compared to a Continuous Infusion of Sufentanyl to Improve Analgesia in Cats Undergoing Unilateral Mastectomy - Vincenzo Cicirelli; Pasquale Debidda; Nicola Maggio; Michele Caira; Daniela Mrenoshki; Giulio G. Aiudi; Giovanni M. Lacalandra (Animals, 2021)
Unilateral mastectomy is a common surgical procedure in feline species and requires postoperative pain management. Our study aimed to evaluate the analgesic efficacy of subarachnoid anaesthesia combined with an intercostal nerve block, in comparison with the use of sufentanyl citrate administered as a constant-rate infusion (CRI). Twenty cats were randomly divided into two groups (n = 10/group) based on the analgesic protocol used: the first received loco-regional anaesthesia with levobupivacaine (LR group), and the second received a CRI of sufentanyl (SUF group). The evaluation criteria during surgery were the need for a bolus of fentanyl in the event of an increased heart rate or increased blood pressure. In the postoperative period, the levels of comfort/discomfort and pain were used to obtain a score according to the UNESP-Botucatu multimodal scale. Subjects who scored above seven received analgesic drug supplementation. Intraoperative analgesia was satisfactory, with good haemodynamic stability in both groups. Four patients in the LR group required an extra dose of methadone after they achieved the sternal decubitus position, whereas those in the SUF group required many more doses. The analgesia achieved in the LR group was more satisfactory than that in the SUF group.